Effects of class‐specific, synthetic, and natural proteinase inhibitors on life‐history traits of the cotton bollworm Helicoverpa armigera. Issue 4 (2nd December 2019) - Kuwar, Suyog S.; Pauchet, Yannick; Heckel, David G.
Abstract: Herbivorous insects have more difficulty obtaining proteins from their food than do predators and parasites. The scarcity of proteins in their diet requires herbivores to feed voraciously, thus heavily damaging their host plants. Plants respond to herbivory by producing defense compounds, which reduce insect growth, retard development, and increase mortality. Herbivores use both pre‐ and postdigestive response mechanisms to detect and avoid plant defense compounds. Proteinase inhibitors (PIs) are one example of plant compounds produced as a direct defense against herbivory. Many insects can adapt to PIs when these are incorporated into artificial diets. However, little is known about the effect of PIs on diet choice and feeding behavior. We monitored the diet choice, life‐history traits, and gut proteinase activity of Helicoverpa armigera larvae using diets supplemented with synthetic and natural PIs. In choice experiments, both neonates and fourth‐instar larvae preferred the control diet over PI‐supplemented diets, to varying degrees. Larvae that fed on PI‐supplemented diets weighed less than those that fed on the control diet and produced smaller pupae. Trypsin‐specific PIs had a stronger effect on mean larval weight than did other PIs. A reduction of trypsin activity but not of chymotrypsin activity was observed in larvae fed on PI‐supplemented diets. Therefore, behavioral avoidance of feeding on plant parts high in PIs could be an adaptation to minimize the impact of this plant's defensive strategy. Abstract : Effect of proteinase inhibitors on the diet choice of the neonate and fourth‐instar Helicoverpa armigera larvae. Highlights: Neonate and fourth‐instar larvae prefer control diet against PIs‐supplemented diets. Mean larval weight was reduced on PIs‐supplemented diets compare to the control diet. Larval weight affected more on trypsin specific PIs than chymotrypsin PIs.